A fast acoustic field mapping approach based on fabry–perot sensor with high‐speed camera. Issue 5 (10th June 2014) - Cong, Bing; Kondo, Kengo; Yamakawa, Makoto; Shiina, Tsuyoshi; Nakajima, Takao; Asao, Yasufumi
Abstract A Fabry–Perot (FP) interferometer‐based ultrasound sensor provides an inherently broadband response and excellent detection sensitivity compared to piezoelectric zirconate titanate (PZT) or polyvinylidene difluoride (PVDF) transducers. It is therefore expected to be used for medical ultrasound imaging and photoacoustic imaging. However, at present, mapping acoustic fields takes much time for scanning, which hinders real‐time measurement. We propose a new approach that utilizes a high‐speed camera (HSC) to map acoustic fields without mechanical scanning and to sample signals of acoustic waves with the shutter of the HSC. Experimental results indicate that acoustic field at the focus of a pulsed 1‐MHz PZT ultrasound transducer can be detected and mapped by using the FP sensor with the HSC. By improving the uniformity of the FP sensor and the exposure time, the frame rate of HSC can be further developed, and this approach should be able to provide a fast acoustic field mapping for high‐resolution biomedical photoacoustic and other ultrasonic imaging. © 2014 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.